Racial and cultural minority experiences and perceptions of health care provision in a mid-western region - Stephane M. Shepherd; Cynthia Willis-Esqueda; Yin Paradies; Diane Sivasubramaniam; Juanita Sherwood; Teresa Brockie (BMC, 2018)
Abstract Background Disparities across a number of health indicators between the general population and particular racial and cultural minority groups including African Americans, Native Americans and Latino/a Americans have been well documented. Some evidence suggests that particular groups may receive poorer standards of care due to biased beliefs or attitudes held by health professionals. Less research has been conducted in specifically non-urban areas with smaller minority populations. Methods This study explored the self-reported health care experiences for 117 racial and cultural minority Americans residing in a Mid-Western jurisdiction. Prior health care experiences (including perceived discrimination), attitudes towards cultural competence and satisfaction with health care interactions were ascertained and compared across for four sub-groups (African-American, Native American, Latino/a American, Asian American). A series of multiple regression models then explored relationships between a concert of independent variables (cultural strength, prior experiences of discrimination, education level) and health care service preferences and outcomes. Results Overall, racial/cultural minority groups (African Americans, Native Americans, Latino/a Americans, and Asian Americans) reported general satisfaction with current healthcare providers, low levels of both health care provider racism and poor treatment, high levels of cultural strength and good access to health care services. Native American participants however, reported more frequent episodes of poor treatment compared to other groups. Incidentally, poor treatment predicted lower levels of treatment satisfaction and racist experiences predicted being afraid of attending conventional health care services. Cultural strength predicted a preference for consulting a health care professional from the same cultural background. Conclusions This study provided a rare insight into minority health care expectations and experiences in a region with comparatively lower proportions of racial and cultural minorities. Additionally, the study explored the impact of cultural strength on health care interactions and outcomes. While the bulk of the sample reported satisfaction with treatment, the notable minority of participants reporting poor treatment is still of some concern. Cultural strength did not appear to impact health care behaviours although it predicted a desire for cultural matching. Implications for culturally competent health care provision are discussed within.